Surgical Management of a Unique Case of Salivary Gland Tumor in a Doberman - Tripathi, Santoshmani D; Rani, Monika; Khandekar, Gajendra S; Gaikwad, Shahir V; Jadhav , Manika (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The primary salivary glands in dogs include the parotid, mandibular, sublingual, and zygomatic glands. Diseases  affecting these glands are relatively rare, with an overall  incidence rate of 0.17% (Carberry et al., 1988). Common  surgical conditions of the salivary glands in dogs include  mucocele, sialadenosis, fistula, sialadenitis, sialolithiasis,  and neoplasia (Johnson, 2008). The parotid and mandibular  salivary glands are most frequently affected, with the parotid  gland being the most commonly involved in canine cases  (Hammer et al., 2001). Salivary gland tumors are categorized  as either benign or malignant, with the majority being  malignant and of epithelial origin (Head and Else, 2002).  The most frequently diagnosed malignant tumors are  adenocarcinomas and carcinomas (Almeida et al., 2010).  Pleomorphic adenomas are rarely reported in dogs and cats  (Head et al., 2003). Diagnosis can be done through fine needle  aspiration cytology, incisional biopsy, and histopathological  examination of excisional biopsy samples (Militerno et al.,  2005). This article describes the surgical management of a  rare salivary gland tumor in a dog.
Keywords: Doberman; Haemato-biochemical